prove that tanA/secA-1+tanA/secA+1=2cosecA
Answers
Answered by
145
LHS = tanA/secA - 1 + tanA/secA + 1
= sinA/cosA / 1/cosA - 1 + sinA/cosA / 1/cosA + 1 [because tan A = sin A / cos A and sec A = 1 / cos A]
= sinA/cosA / (1 - cosA) / cosA + sinA/cosA / (1 + cosA) / cos A
= sinA / 1 - cosA + sinA / 1 + cos A
= [sinA (1 + cosA) + sinA (1 - cosA)] / (1 - cosA) (1 + cosA)
= [sinA + sinAcosA + sinA - sinAcosA] / 1 - cos(sq) A
= 2sinA / sin(sq) A [From identity: sin(sq) A + cos(sq) A = 1]
= 2 / sin A
= 2 x 1 / sinA
=2 cosecA
= sinA/cosA / 1/cosA - 1 + sinA/cosA / 1/cosA + 1 [because tan A = sin A / cos A and sec A = 1 / cos A]
= sinA/cosA / (1 - cosA) / cosA + sinA/cosA / (1 + cosA) / cos A
= sinA / 1 - cosA + sinA / 1 + cos A
= [sinA (1 + cosA) + sinA (1 - cosA)] / (1 - cosA) (1 + cosA)
= [sinA + sinAcosA + sinA - sinAcosA] / 1 - cos(sq) A
= 2sinA / sin(sq) A [From identity: sin(sq) A + cos(sq) A = 1]
= 2 / sin A
= 2 x 1 / sinA
=2 cosecA
siddhartharao77:
Nice Explanation.
Answered by
29
Step-by-step explanation:
This is the answer
Attachments:
![](https://hi-static.z-dn.net/files/d90/a179643c3f08c0c054ff14625a103233.jpg)
![](https://hi-static.z-dn.net/files/d08/5fe0fd9c07e898f61dc53751c5ade2f7.jpg)
Similar questions